Factors Influencing Brand Choice of Mobile Phones in Kathmandu Valley - Chapagain, Kishan; Sawagvudcharee, Ousanee (Nepalese Journal of Management Science and Research, 2019)
The main aim of the study is to investigate the factor influencing the brand choice of mobile phone in Kathmandu valley. The study identifies the how brand effect in selection of mobile phone. For the efficient completion of the research a sample of 385 customers were taken from Kathmandu valley. Simple random sampling method was used where every element of the study population had equal and non-zero chance of being selected as a sample of the study. The independent study is completed using a blend of descriptive and causal comparative research design. Quantitative method is used in the research where the questionnaires are close ended with fixed options to be selected. In the present research study, I found that brand attitude, brand image, brand attributes and reference group have positive significant effect on selection of mobile phone brand.